How do archaeologists write about racism? Computational text analysis of 41 years of Society for American Archaeology annual meeting abstracts - Park, Gayoung; Wang, Li-Ying; Marwick, Ben (Antiquity, 2022)
How often, and in what contexts, have archaeologists discussed racism over the last four decades? Do societal events lead to sustained discussions of racism among the academic community? Here, the authors seek to answer these questions by applying computational text analysis methods to 68176 abstracts from 41 meetings of the Society for American Archaeology. Discussions of racism are found to be rare—usually a passing mention in the context of broader social issues. Historical archaeologists have addressed racism more frequently than other archaeologists. The results form a baseline against which the discipline's engagement with racism as a research theme and with anti-racist strategies might be tracked.